2007
DOI: 10.1007/s10856-007-3314-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hot water and heat treatment on the apatite-forming ability of titania films formed on titanium metal via anodic oxidation in acetic acid solutions

Abstract: Titanium and its alloys have been widely used for orthopedic implants because of their good biocompatibility. We have previously shown that the crystalline titania layers formed on the surface of titanium metal via anodic oxidation can induce apatite formation in simulated body fluid, whereas amorphous titania layers do not possess apatite-forming ability. In this study, hot water and heat treatments were applied to transform the titania layers from an amorphous structure into a crystalline structure after tit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 30 publications
1
32
0
1
Order By: Relevance
“…The results demonstrated that the surface roughness of treated samples was improved by the formation of sodiumtitanate layer over the modified surface and it was useful for the enhancement of biocompatibility of alkali-heat treated Ti alloy 70 . Cui et al 71 transformed the amorphous titania layer into a crystalline structure by treating with hot water and heat. The capability of the formation of apatite layer was studied through SEM and XRD analysis.…”
Section: Alkali-heat Treatmentmentioning
confidence: 99%
“…The results demonstrated that the surface roughness of treated samples was improved by the formation of sodiumtitanate layer over the modified surface and it was useful for the enhancement of biocompatibility of alkali-heat treated Ti alloy 70 . Cui et al 71 transformed the amorphous titania layer into a crystalline structure by treating with hot water and heat. The capability of the formation of apatite layer was studied through SEM and XRD analysis.…”
Section: Alkali-heat Treatmentmentioning
confidence: 99%
“…To date, titanium materials have been pretreated with water, acidic and alkaline chemicals, thermal and electrochemical oxidation, or their combination to improve apatite deposition. 4,6,[8][9][10][11] Other technologies, such as single-and multiple-layer splat…”
Section: Introductionmentioning
confidence: 99%
“…This has been attributed to an abundance of surface hydroxyl groups and high specific surface area [15][16][17]. However, poor crystallinity of such TiO 2 layers may limit their PCA, and while subsequent heat treatments may improve the crystallinity, such treatments eradicate beneficial hydroxyl groups and reduce the specific surface area [18,19]. Direct H 2 O 2 -oxidation of Ti is also known to produce a Ti-peroxy gel with associated superoxide radicals (Ti(IV)O 2 -) [20][21][22].…”
Section: Introductionmentioning
confidence: 99%